Communication In The Family Dictates Quran Surah An Naml In Shaping Children's Character - Taufiqurrahman Taufiqurrahman; Zainal Arifin; Mailin Mailin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Communication in the family is the exchange of messages, both verbally and nonverbally, which aims to strengthen understanding and relationships between family members. This process results in an emotional bond of warmth, affection, and love between them. This study describes communication within the family sphere contained in the Quran surah An Naml, with the main aim of discussing its influence on the formation of children's character. The method used in this study is a qualitative descriptive approach using sources from literature, known as library research. Through the analysis of the views of Wahbah Zuhaili and Zainal Arifin Zakaria, researchers can identify various models of approaches that can be applied by parents in shaping the character of children in the family environment, as explained in surah An Naml.